2009
DOI: 10.1097/bpb.0b013e32832f0648
|View full text |Cite
|
Sign up to set email alerts
|

Nonunion of the ulna after elastic stable intramedullary nailing for unstable forearm fractures: a case series

Abstract: Elastic stable intramedullary nailing (ESIN) for displaced forearm fractures in children has shown good results over the last two decades. To our knowledge, nonunion as complications after ESIN fixation of displaced forearm fractures is not well reported in English literature. In our institute, and over a period of 10 years, we identified three cases of nonunion of the ulna after ESIN fixation of unstable and displaced forearm both bone fractures. Two patients had closed fractures and one patient had an open f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…They recorded postoperative complications in three patients, a superficial pin entry site infection 16 . Garg et al reported 21 pediatric patient treated with ESIN for displaced and unstable diaphyseal forearm fractures 22 . All their fixations were protected in an above elbow plaster cast.…”
Section: Discussionmentioning
confidence: 99%
“…They recorded postoperative complications in three patients, a superficial pin entry site infection 16 . Garg et al reported 21 pediatric patient treated with ESIN for displaced and unstable diaphyseal forearm fractures 22 . All their fixations were protected in an above elbow plaster cast.…”
Section: Discussionmentioning
confidence: 99%
“…Two cases of nonunion reported by Moez et al were both treated with plating following removal of ESIN [9]. However, we have not found any reports using ESIN to treat nonunion of diaphyseal forearm fractures in children as described in our case.…”
Section: Discussionmentioning
confidence: 62%
“…Moez et al [9] recently reported three cases of ulna nonunion following ESIN of which all occurred at the mid-shaft. The reduction method was an open reduction in all their cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, intramedullary nailing has significant advantages over plate fixation including less tissue disruption, smaller incisions, shorter operative time, a lower refracture rate, and increased ease of hardware removal [38]. Complications including nonunion, loss of motion, compartment syndrome, and others have also been reported [4,9,13,[38][39][40][41]. In contrast, plate fixation has the advantage of a more rigid, anatomic repair of the fracture.…”
Section: Discussionmentioning
confidence: 94%